The Effect of the Midlatitude Electron Density Trough on the Ionospheric Conductivities - Timocin, Erdinc; Unal, Ibrahim; Yesil, Ali (Springer International Publishing Ag, 2019)
In this study, we have investigated the effect of midlatitude electron density trough on ionospheric conductivities for different altitudes. For this purpose, parallel conductivity (sigma (0)), Pedersen conductivity (sigma (1)) and Hall conductivity (sigma (2)) data were calculated by using the International Reference Ionosphere (IRI) model for seven different geographic coordinates in the midlatitude region of the northern hemisphere during the June and December solstices of 1972. Planetary geomagnetic activity index () data are used as a geomagnetic activity indicator. These conductivity values computed for each position were classified according to geomagnetic active () and geomagnetic quiet () conditions; and these values were examined according to invariant magnetic latitudes (I >) for different heights, seasonal, geomagnetic activity and local times. From the analysis results, it is found that the midlatitude electron density trough does not have any effects on sigma (0) for all situations, but the trough is influential on sigma (1) and sigma (2) during night hours of the December solstices. In addition, it was observed that the trough increased its effect on sigma (1) and sigma (2) with the increasing geomagnetic activity level and altitude for December solstices.
Keywords: Ionosphere; Ionospheric conductivities; Midlatitude electron density trough; Magnetosphere